Climate Change and Social Forestry: An Overview of CIFOR Research on Enhancing Resilience in Boreal and Tropical Forest Landscape - Daisuke Naito; Moira Moeliono; Vladimir Chakov; Victoria Kuptsova; Kusin Kitso; Walter Lintangah; Ricky Martin; Nina Yulianti (Japan International Research Center for Agricultural Sciences, 2021)
The climate crisis highlights the importance of forests in both mitigating and adapting to climate change, as well as in supporting the UN’s Sustainable Development Goals (SDGs). To promote the better understanding and valuing of the critical role forests play, and to develop holistic approaches to protecting and maintaining them, the Center for International Forestry Research (CIFOR) has adopted the mission “to bring scientific knowledge to bear on major decisions affecting the world’s tropical forests and the people who depend on them”. This paper highlights an important topic in CIFOR’s research portfolio – forests’ diverse roles in climate change mitigation and adaptation and how forest governance ensures the equitable and sustainable wellbeing of people, both locally and globally. As one of the founding donor countries of CIFOR, the Government of Japan has consistently supported CIFOR’s research through Japanese scientists collaborating in research projects and/or serving as members of CIFOR’s Board. This paper, therefore, specifically highlights research projects funded directly by the Government of Japan, in particular.